Examining energy-efficient recuperative braking modes of traction asynchronous frequency-controlled electric drives - Sinchuk, Oleg; Kozakevich, Igor; Kalmus, Dmytro; Siyanko, Roman (Eastern-European Journal of Enterprise Technologies, 2017)
Energy efficiency is an important task of modern society due to the finite amount of mineral resources and environmental problems. Even more important this task is for electric transport vehicles with autonomous energy sources since its successful solution affects performance indicators of these systems. Particularly promising in the context of this problem is the question of energy optimization in the recuperative braking modes because it makes it possible to return kinetic energy, accumulated by transport vehicle, to the source. In present paper we analyzed equations of state of asynchronous motor under static operation mode in order to obtain analytical dependences that describe motor performance under recuperative braking mode. Conducted analysis allowed us to establish an interrelation between the limits in magnitudes of voltage and current, parameters of equivalent circuit and the torque generated at such work. By examining the received patterns, we calculated the magnitude of minimum angular velocity at which it is possible to realize the mode of recuperative braking, that is, the generation of electrical energy by motor to the power supply. A special benefit of present work is that the obtained dependences were explored both for the work at angular velocity that is lower than the base one and for a field weakening mode since in electric drives of transport vehicles of alternating current the use of two-zone control is quite common. By applying mathematical modeling, we confirmed the results received in present work.